Financial Sector Assessment Program : Malaysia - IOSCO Objectives and Principles of Securities Regulation - World Bank; International Monetary Fund (World Bank, Washington, DC, 2013)
The Securities Commission Malaysia (SC), as the supervisor of the capital markets, has developed a robust supervisory framework that exhibits high levels of implementation of the International Organization of Securities Commissions Objectives and Principles of Securities Regulation (IOSCO Principles) in most areas. The SC's independence will be buttressed by some changes to the legal provisions on removal of commission members and to protections given to the members of the commission and to its staff. The disclosure deadlines for issuers and their substantial shareholders should be adjusted to reflect international best practices. The new frameworks for oversight of credit rating agencies (CRAs) and the Federation of Investment Managers Malaysia (FIMM) should be implemented in full by carrying out on-site inspections as presently planned. At this stage in the jurisdiction's development, consideration should also be given to putting in place the pre-conditions that will enable the SC to ease up gradually on the intensity of its direct involvement in the day-to-day operations of the capital market and its participants.